USAHA PERPUSTAKAAN PROKLAMATOR BUNG KARNO DALAM MEREKAM SEJARAH LISAN UNTUKMELESTARIKAN PENGETAHUAN TENTANG SUKARNO (1901–1970): PENERAPAN SEJARAH LISAN DALAM MEREKAM PENGETAHUAN SOSOK MARHAEN DI BANDUNG - Aji Subekti (Perpustakaan Nasional RI, 2019)
The role of oral history in preserving the knowledge of Sukarno is very important to fulfil the lack of written sources. This paper is a conceptual paper and the application of recording the knowledge of Sukarno that focuses on Marhaen,as a figure, using oral history based on